Perspective-Taking and Empathy Mitigate Family-of-Origin Risk for Electronic Aggression Perpetration Toward Dating Partners: A Brief Report. Issue 3 (February 2021) - Ramos, Michelle C.; Miller, Kelly F.; Moss, Ilana K.; Margolin, Gayla
Electronic dating aggression among emerging adults is prevalent and has adverse consequences, yet factors that increase or decrease the risk for perpetrating electronic aggression against a romantic partner are understudied. This investigation advances the literature in two novel ways. First, based on intergenerational transmission of violence theories, we tested the link between family-of-origin aggression (FOA) history and electronic aggression toward romantic partners, using a diverse sample of emerging adults. Second, we examined whether perspective-taking and empathy each moderated the association between FOA and electronic dating aggression and explored the moderating role of gender. Participants included 359 undergraduate students (50% female; 42% White) from an urban university. Results indicated that greater FOA during childhood was associated with perpetrating greater electronic aggression against romantic partners. Furthermore, significant interactions indicated that perspective-taking and empathy separately buffered these associations. Youth from aggressive families did not exhibit increased electronic dating perpetration when they had higher perspective-taking or empathy. Males were especially sensitive to the protective effects of perspective-taking. Findings highlight potential points of intervention (i.e., cognitive and affective empathy training) to decrease electronic aggression in romantic relationships and break intergenerational cycles of aggression.